Public assessments of police during the COVID-19 pandemic: the effects of procedural justice and personal protective equipment. Issue 1 (16th July 2021) - Sandrin, Ryan; Simpson, Rylan
Abstract : Purpose: The COVID-19 pandemic has presented many challenges for contemporary police. The present research examines public assessments of police responsibility and performance during the pandemic using a procedural justice paradigm. Design/methodology/approach: Participants ( N  = 104) rated images of a police officer, including when using different items of personal protective equipment (PPE), along the core dimensions of procedural justice. Participants then completed survey questions about their assessments of the police's responsibility and performance during the COVID-19 pandemic. Findings: Findings from our regression analyses indicate that participants' perceptions of procedural justice are positively related to their assessments of police responsibility and performance. Our findings also indicate that participants' perceptions of procedural justice can be affected by the police's use of different items of PPE, including face masks, face shields, goggles and medical gloves. Originality/value: The present research uses procedural justice, a well-trodden paradigm from past empirical works, to examine perceptions of police amidst a time of much societal change. The findings present important practical implications for police who must continue to manage public perceptions while providing service during the pandemic.